Differential spatiotemporal gait effects with frequency and dopaminergic modulation in STN-DBS - Ramdhani, Ritesh A.; Watts, Jeremy; Kline, Myriam; Fitzpatrick, Toni; Niethammer, Martin; Khojandi, Anahita (Frontiers in Aging Neuroscience, 2023)
The spatiotemporal gait changes of advanced Parkinson's Disease (PD) remain a treatment challenge and has variable responses to L-dopa and subthalamic deep brain stimulation STN-DBS. The purpose of this study is to determine whether low frequency (LFS; 60Hz) STN-DBS elicits a differential response to high frequency (HFS;180hz) in spatiotemporal gait kinematics.Advanced PD subjects with chronic STN-DBS were evaluated in both the OFF and ON medication states with LFS and HFS stimulation. Randomization of electrode contact pairs and frequency conditions were conducted. Instrumented Stand and Walk assessments were carried out for every stimulation/medication condition. LM-ANOVA was employed for analysis.Twenty-two PD subjects participated with a mean age(SD) of 63.9(9). Significant interactions between frequency (both LFS and HFS) and electrode contact pairs (particularly ventrally located contacts) were observed for both spatial (foot elevation, toe-off angle, stride length) and temporal (foot speed, stance, single limb support (SLS) and foot swing) gait parameters. A synergistic effect was also demonstrated with L-dopa and both HFS and LFS for right SLS, left stance, left foot swing, right toe-off angle, and left arm range of motion. HFS produced significant improvement in trunk and lumbar range of motion compared to LFS.The study provides evidence of synergism of L-dopa and STN-DBS on lower limb spatial and temporal measures in advanced PD. HFS and LFS STN-DBS produced equivalent effects among all other tested lower limb gait features. HFS produced significant trunk and lumbar kinematic improvements.